Saggi di anglistica e americanistica Percorsi di ricerca - Fiorenzo Fantaccini (Strumenti per la didattica e la ricerca, 2012)
The third volume of Saggi di anglistica e americanistica is the last in the series published under the aegis of the University of Florence PhD course in English and American Studies which, after 25 years, will terminate its activities in 2013. This last collection once again attests to the worth of the PhD's educational programme and aims: it brings together the essays produced by ten young scholars over the last three years of research, in view of preparing their PhD dissertations. They are essays that range from literary phenomena and their historic, linguistic and socio-cultural contexts, to problems posed by texts from Anglo-American to South African, Australian and Caribbean cultures, confirming the variety of the Florence PhD students' research interests and approaches. Saggi di anglistica e americanistica. Percorsi di ricerca by Fiorenzo Fantaccini, Ornella De Zordo is licensed under a Creative Commons Attribuzione-Non commerciale-Non opere derivate 2.5 Italia License. Based on a work at www.fupress.com.